2015
DOI: 10.1002/ange.201505946
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Primary Amine/Palladium Dual Catalysis for Asymmetric Allylic Alkylation of β‐Ketocarbonyl Compounds with Allylic Alcohols

Abstract: An efficient dual catalytic system composed of ac hiral primary amine and ap alladium complex was developed to promote the direct asymmetric allylic alkylation (AAA) of b-ketocarbonyl compounds.I np articular,t he synergistic dual catalytic system enabled the AAA reaction of challenging acyclic aliphatic ketones,s uch as b-ketocarbonyl compounds and 1,3-diketones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…The presence of stoichiometric amount of amine/TfOH would facilitate the hydropalladation process, hence the formation of addition product 4a in this instance. In accordance with our previous studies, [61][62][63][64] a steric model could be proposed to account for the observed stereoselectivity. 64 Bulkiness from the protonated amino moiety and the space-demanding palladium intermediate (II or V) both contribute to the stereocontrol.…”
Section: Investigation Of Mechanismsupporting
confidence: 88%
“…The presence of stoichiometric amount of amine/TfOH would facilitate the hydropalladation process, hence the formation of addition product 4a in this instance. In accordance with our previous studies, [61][62][63][64] a steric model could be proposed to account for the observed stereoselectivity. 64 Bulkiness from the protonated amino moiety and the space-demanding palladium intermediate (II or V) both contribute to the stereocontrol.…”
Section: Investigation Of Mechanismsupporting
confidence: 88%
“…In the last decade, great efforts have been conducted on this important transformation in order to replace the traditionally employed alcohol derivatives (such as carbonates, acetates, phosphates…) as substrates, for the more readily available and environmentally friendly allylic alcohols . However, despite the enormous progresses already accomplished in the area, the asymmetric allylic alkylation reaction, also known as asymmetric Tsuji‐Trost reaction, of 1,3‐dicarbonyl compounds, employing such substrates is still undeveloped and, to the best of our knowledge, there are only a handful of works reported in the literature on this respect being, most of them, catalyzed by expensive transition‐metal based catalytic systems . In addition, even scarcer is the use of unsymmetrical 1,3‐dicarbonyl compounds, such as β ‐keto esters, which would render two consecutive all‐carbon stereocenters, as nucleophiles…”
Section: Methodsmentioning
confidence: 99%
“…[ 29‐33 ] These catalysts also work effectively in concert with other catalytic systems including photoredox, electrochemical, metal catalysis as well as another organocatalysts, thus significantly expanding their catalytic spaces. [ 34‐41 ]…”
Section: Bi/multi‐function Strategy: Development and Application Of C...mentioning
confidence: 99%